Bend-resistant large mode area fiber with novel segmented cladding. (1st January 2018) - Ma, Shaoshuo; Ning, Tigang; Pei, Li; Li, Jing; Zheng, Jingjing
Highlights: A novel segmented cladding fiber (SCF) is proposed. The bend-resistance and large mode area property are demonstrated. A large mode area of 700 μm 2 is achieved. The fiber has better single-mode operation than traditional SCF. Abstract: A novel structure of segment cladding fiber (SCF) with characteristics of bend-resistance and large-mode-area (LMA) is proposed. In this new structure, the high refractive index (RI) core is periodically surrounded by high RI fan-segmented claddings. Numerical investigations show that effective single-mode operation of the proposed fiber with mode field area of 700 μm 2 can be achieved when the bending radius is 15 cm. Besides, this fiber is insensitive to the bending orientation at the ranging of [−180°, 180°]. The proposed design shows great potential in high power fiber lasers and amplifiers with compact structure.